Money is time: On the possibility of critique after neoliberalism - Leigh Claire La Berge (Finance and Society, 2018)
What is the relationship now, and what should the relationship be, between a social-theory oriented critique of neoliberalism, such as the one Konings provides, and other disciplines? In this review essay, I suggest some of the conversations we might form between Konings' text and texts of a more Marxist variety, including Alfred Sohn-Rethel's Intellectual and Manual Labor, as well as contemporary literary studies texts, including Mary Poovey's Genres of the Credit Economy and Fredric Jameson's “Culture and Finance Capital”. In each potential pairing, I suggest a possible relationship between historical time, financial time, and narrative itself.